2021
DOI: 10.1172/jci.insight.145928
|View full text |Cite
|
Sign up to set email alerts
|

Chronic HIV infection induces transcriptional and functional reprogramming of innate immune cells

Abstract: Chronic inflammation and immune dysfunction play a key role in the development of non-AIDS related comorbidities. The aim of our study was to characterize the functional phenotype of immune cells in people living with HIV (PLHIV). We enrolled a cross-sectional cohort study of PLHIV on stable antiretroviral therapy and healthy controls. We assessed ex vivo cytokine production capacity and transcriptomics of monocytes and T-cells upon bacterial, fungal and viral stimulation. PLHIV exhibited an exacerbated pro-in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
55
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(71 citation statements)
references
References 74 publications
(113 reference statements)
10
55
0
Order By: Relevance
“…As discussed above, naïve T cells are able to differentiate into different Th subsets depending on the cytokine environment (42). We previously showed that PLHIV in our cohort exhibited a pro-inflammatory profile with increased levels of hsCRP (p=0.00022) and sCD14 (a marker of monocyte activation, p=0.0025; Figure 5A) as well as markedly elevated monocyte-derived cytokine responses, particularly IL-1b (20). Such a pro-inflammatory cytokine environment may push the differentiation of naive CD4+ cells into Th17 cells (42).…”
Section: Microbial Translocation Inflammation and Th17 Differentiatisupporting
confidence: 54%
See 2 more Smart Citations
“…As discussed above, naïve T cells are able to differentiate into different Th subsets depending on the cytokine environment (42). We previously showed that PLHIV in our cohort exhibited a pro-inflammatory profile with increased levels of hsCRP (p=0.00022) and sCD14 (a marker of monocyte activation, p=0.0025; Figure 5A) as well as markedly elevated monocyte-derived cytokine responses, particularly IL-1b (20). Such a pro-inflammatory cytokine environment may push the differentiation of naive CD4+ cells into Th17 cells (42).…”
Section: Microbial Translocation Inflammation and Th17 Differentiatisupporting
confidence: 54%
“…Prior studies have shown that untreated HIV infection results in a massive depletion of Th17 cells from the peripheral blood and the mucosa ( 9), a process that may partially be reversed by cART (46)(47)(48). We recently showed that PLHIV from the same cohort exhibited a pro-inflammatory profile with increased monocytederived cytokines, particularly IL-1b (20). IL-1b and IL-6 are among the critical cytokines driving differentiation of Th17 ( 42), and we postulate that these cytokines may have contributed to the higher circulating Th17 numbers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…BDG assays are now widely used as diagnostic tools for identifying mycosis in clinical settings ( 3 5 ). Recent studies have shown that circulating BDG levels are linked to immune activation and inflammation in people living with chronic conditions that induce epithelial gut damage and subsequent microbial translocation such as CMV and HIV infections ( 6 9 ). A growing body of literature has highlighted the capacity of BDG to induce long-term epigenetic reprogramming in innate immune cells, termed trained immunity, which leads to an adjusted response to a subsequent challenge and to some metabolic changes, including a switch from oxidative phosphorylation to aerobic glycolysis ( 10 , 11 ).…”
Section: Introductionmentioning
confidence: 99%
“…BDG assays are now widely used as diagnostic tools for identifying mycosis in clinical settings (3)(4)(5). Recent studies have shown that circulating BDG levels are linked to immune activation and inflammation in people living with chronic conditions that induce epithelial gut damage and subsequent microbial translocation such as CMV and HIV infections (6)(7)(8)(9). A growing body of literature has highlighted the capacity of BDG to induce long-term epigenetic reprogramming in innate immune cells, termed trained immunity, which leads to an adjusted response to a subsequent challenge and to some metabolic changes, including a switch from oxidative phosphorylation to aerobic glycolysis (10,11).…”
Section: Introductionmentioning
confidence: 99%